Matéria orgânica e atributos químicos em solo de tabuleiros costeiros sob diferentes coberturas vegetais - Ribeiro, Paulo Henrique (2011)
The conversion of native vegetation in agricultural and forest crops results in changes in soil properties. The aimed was to assess the dynamic attributes of a Yellow Oxisol under differents vegetation covers in the Coastal Tableland. Soil samples were collected at depths of 0-10, 10-20 and 20-40 cm in June 2011 in Sooretama, ES, considering four soil vegetation covers: native forest, coffee monoculture, coffee-cedar intercropping, cocoa-cedar intercropping. The experimental design was completely randomized with three replications in split-plot. The following soil atributes were evaluated: water pH; available phosphorus; exchangeable potassium, calcium and magnesium; aluminum; potential acidity; bases content; effective and potential cation exchange capacity; base and aluminum saturation; total organic carbon (TOC); total nitrogen (TN); water-soluble carbon (WSC); C/N and TOC/WSC ratio; light organic matter; TOC and TN stocks. The litter pool was also measured, and based on dry matter yield and nutrient content the same, was calculated the accumulation of each nutrient. The results were submitted to analysis of variance and differences between medium contrasts compared by F-test, verifying a statistical significance (1 and 5%) and trend (20%). The experimental results showed that vegetation covers behaved differently to certain soil attributes. The forest was the cover that most favored the carbon and nitrogen stocks in the soil, demonstrated by higher total organic carbon and total nitrogen, litter pool, water-soluble carbon and light organic matter. Crops demonstrated the potential for carbon and nitrogen stocks in soil. Soil chemical conditions of coffee monoculture were the best for the plant development. The high acidity, high levels of aluminum and low availability of nutrients in the soil under forest reflected its natural condition. The agroforestry consortia had similar condition to soil fertility. However, differed as to litter pool and nutrients in litter